L-Citrullinato-Bipyridine and L-Citrullinato-Phenanthroline Mixed Copper Complexes: Synthesis, Characterization and Potential Anticancer Activity - Diego Ramírez-Contreras; Sergio Vázquez-Rodríguez; Amalia García-García; Lisset Noriega; Angel Mendoza; Brenda L. Sánchez-Gaytán; Francisco J. Meléndez; María Eugenia Castro; Maura Cárdenas-García; Enrique González-Vergara (Pharmaceutics, 2024)
Citrulline (C6H13N3O3) is an amino acid found in the body as a zwitterion. This means its carboxylic and amine groups can act as Lewis donors to chelate metal cations. In addition, citrulline possesses a terminal ureido group on its aliphatic chain, which also appears to coordinate. Here, two new mixed complexes of citrulline were made with 1,10-phenanthroline and 2,2′-bipyridine. These compounds, once dissolved in water, gave aquo-complexes that were subject to DFT studies and in vitro toxicity studies on cancer cell lines (HeLa, MDA-MB-231, HCT 15, and MCF7) showed promising results. Docking studies with DNA were also conducted, indicating potential anticancer properties.